Pengaruh Bimbingan Orang Tua dan Self Control Terhadap Perilaku Menabung Mahasiswa - Utari Melvianda; Elvi Rahmi (Jurnal Ecogen, 2023)
This research objective to determine and analyze: (1) The influence of parental guidance and self-control on the saving behavior of students at the Faculty of Economics, Padang State University. (2) The Influence of Parental Guidance on the Saving Behavior of Students at the Faculty of Economics, Padang State University. (3) The Influence of Self Control on the Saving Behavior of Students at the Faculty of Economics, Padang State University. This type of research is associative descriptive research. The population in this study were students from the Faculty of Economics, Padang State University. The sample used was 98 students using probability sampling. The type of data in this research is primary data. The data collection technique used is a questionnaire, the data that has been collected is analyzed using descriptive analysis. This research uses Multiple Regression analysis. The results of this research show that parental guidance and self-control have a significant effect on the saving behavior of students at the Faculty of Economics, Padang State University.